High Mobility Reactive Sputtered CuxO Thin Film for Highly Efficient and Stable Perovskite Solar Cells - Mohammad Aminul Islam; Yasmin Abdu Wahab; Mayeen Uddin Khandaker; Abdullah Alsubaie; Abdulraheem S. A. Almalki; David A. Bradley; Nowshad Amin (Crystals, 2021)
Copper oxide (CuxO) films are considered to be an attractive hole-transporting material (HTM) in the inverted planar heterojunction perovskite solar cells due to their unique optoelectronic properties, including intrinsic p-type conductivity, high mobility, low-thermal emittance, and energy band level matching with the perovskite (PS) material. In this study, the potential of reactive sputtered CuxO thin films with a thickness of around 100 nm has been extensively investigated as a promising HTM for effective and stable perovskite solar cells. The as-deposited and annealed films have been characterized by using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Photoluminescence (PL), UV-Vis spectroscopy, and Hall-effect measurement techniques. The significant change in structural and optoelectronic properties has been observed as an impact of the thermal annealing process. The phase conversion from Cu2O to CuO, including grain size increment, was observed upon thermal annealing. The transmittance and optical bandgap were found to vary with the films’ crystallographic transformation. The predominant p-type conductivity and optimum annealing time for higher mobility have been confirmed from the Hall measurement. Films’ optoelectrical properties were implemented in the complete perovskite solar cell for numerical analysis. The simulation results show that a 40 min annealed CuxO film yields the highest efficiency of 22.56% with a maximum open-circuit voltage of 1.06 V.